High-fat meal effect on LDL, HDL, and VLDL particle size and number in the Genetics of Lipid-Lowering drugs and diet network (GOLDN): an interventional study. - Wojczynski, Mary K.; Glasser, Stephen P.; Oberman, Albert.; Kabagambe, Edmond K.; Hopkins, Paul N.; Tsai, Michael Y.; Straka, Robert J.; Ordovas, Jose M.; Arnett, Donna K. (2016)
Background: Postprandial lipemia (PPL) is likely a risk factor for cardiovascular disease but these changes have not been well described and characterized in a large cohort. We assessed acute changes in the size and concentration of total and subclasses of LDL, HDL, and VLDL particles in response to a high-fat meal. Participants (n = 1048) from the Genetics of Lipid-Lowering Drugs and Diet Network (GOLDN) Study who ingested a high-fat meal were included in this analysis. Lipids were measured at 0 hr (fasting), 3.5 hr, and 6 hr after a standardized fat meal. Particle size distributions were determined using nuclear magnetic resonance spectroscopy. Analyses were stratified by baseline triglycerides (normal vs. elevated) and gender. The effect of PPL on changes in lipoprotein subclasses was assessed using repeated measures ANOVA.; Keywords: postprandial lipemia, lipoprotein particles, NMR, high-fat meal.; Springer Open.